2010
DOI: 10.1007/s10006-010-0233-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the mesio-buccal gingival sulcus depth of the upper central incisors in patients submitted to surgically assisted maxillary expansion

Abstract: The gingival sulcus depths increased during the initial post-operative periods. The SAME procedure increased the gingival sulcus depth of the upper central incisors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 31 publications
0
4
0
10
Order By: Relevance
“…2 The best results in the treatment of skeletally mature individuals have been achieved using SARPE, 3 whereas nonsurgically assisted rapid maxillary expansion (NSARPE) in these individuals has been associated with complications, such as buccal tilt and displacement of the teeth that anchor the expander. [4][5][6][7] SARPE techniques and variations have been described elsewhere, [2][3][4][5][6][7][8][9][10][11][12] and studies have confirmed that the activation of the tooth-borne (Hyrax) or tooth-tissue-borne (Haas) expanders after osteotomies dissipates tensions responsible for the lateral movement of the maxilla and all adjacent structures, such as the teeth and the bones of the face and skull, [13][14][15] which affects the nasal cavity, 16 nasal septum, 17 lateral walls and floor of the nose 18 and nasal area, 19 as well as the upper lip, 20 alar base, 21 gingiva, 22 and facial soft tissues. 23 This study used finite element analysis (FEA) to evaluate the distribution of tensions in the anchor teeth of a tooth-tissueborne expander when different types of osteotomies were simulated.…”
mentioning
confidence: 99%
“…2 The best results in the treatment of skeletally mature individuals have been achieved using SARPE, 3 whereas nonsurgically assisted rapid maxillary expansion (NSARPE) in these individuals has been associated with complications, such as buccal tilt and displacement of the teeth that anchor the expander. [4][5][6][7] SARPE techniques and variations have been described elsewhere, [2][3][4][5][6][7][8][9][10][11][12] and studies have confirmed that the activation of the tooth-borne (Hyrax) or tooth-tissue-borne (Haas) expanders after osteotomies dissipates tensions responsible for the lateral movement of the maxilla and all adjacent structures, such as the teeth and the bones of the face and skull, [13][14][15] which affects the nasal cavity, 16 nasal septum, 17 lateral walls and floor of the nose 18 and nasal area, 19 as well as the upper lip, 20 alar base, 21 gingiva, 22 and facial soft tissues. 23 This study used finite element analysis (FEA) to evaluate the distribution of tensions in the anchor teeth of a tooth-tissueborne expander when different types of osteotomies were simulated.…”
mentioning
confidence: 99%
“…Além da osteotomia na região alveolar da sutura intermaxilar, de acordo Assis et al (2011) de um decréscimo aos níveis pré-operatórios nos períodos de 6 e 12 meses. Para Enoki et al (2006), esse decréscimo ocorreu pela compensação parcial da mucosa dos cornetos inferiores (edema), não permitindo real aumento da area nasal minima, porém reduzindo a reistência nasal, não suportando a idéia da execução da expansão de maxila meramente para correcão de problemas respiratórios.…”
Section: Palatino (Figura 8)unclassified
“…The treatment of TMD in individuals with skeletal maturity is surgically assisted palatal expansion (SAPE) and this treatment has shown good results4, even with the description of different surgical techniques 2 . The effects of SAPE are observed not only in the dental arch 5 , but also in the adjacent structures [6][7][8][9][10] and mandibular dental arch 11 . The procedure is not free of complications, such as the occurrence of pain in the temporomandibular joint (TMJ) in 3% of the cases, mobility (3%) and loss (3%) of the upper central incisors, sinusitis (6%), paresthesia (3%), bleeding (3%), external resorption of teeth (3%) and displacement and tilt of the teeth (3%) 12 .…”
Section: Introductionmentioning
confidence: 99%